Book review: Coles, A., Gray, L. and Momsen, J., editors, 2015: The Routledge Handbook of Gender and Development. (July 2018) - Kumar, Ankit
Coles, A., Gray, L. and Momsen, J., editors, 2015: The Routledge Handbook of Gender and Development . London/New York, NY: Routledge. 594 pp. £190. ISBN: 9780415829083 (Hardcover).